2013
DOI: 10.4236/jbise.2013.68a2004
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell therapy for idiopathic pulmonary fibrosis: How far are we from the bench to the bedside?

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 83 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…In this study, we demonstrated the safety and efficacy of an intrinsic lung‐derived cell therapy product in a bleomycin‐induced rat model of pulmonary fibrosis. Allogeneic cell therapy for lung diseases has been pursued in previous research endeavors and current phase I clinical trials, but almost exclusively with MSCs . In contrast, the use of intrinsic distal lung‐derived cells represents a new approach .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we demonstrated the safety and efficacy of an intrinsic lung‐derived cell therapy product in a bleomycin‐induced rat model of pulmonary fibrosis. Allogeneic cell therapy for lung diseases has been pursued in previous research endeavors and current phase I clinical trials, but almost exclusively with MSCs . In contrast, the use of intrinsic distal lung‐derived cells represents a new approach .…”
Section: Discussionmentioning
confidence: 99%
“…Allogeneic cell therapy for lung diseases has been pursued in previous research endeavors and current phase I clinical trials, but almost exclusively with MSCs . In contrast, the use of intrinsic distal lung‐derived cells represents a new approach . LSCs benefit from a self‐agglomerating 3D sphere culture system which has been shown to recapitulate the in vivo environment and enhance the innate stemness of cells .…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF), the most common type of interstitial lung disease (ILD), is a chronic, irreversible disease that is characterized by exaggerated matrix deposition, lung architecture distortion and honeycombing . As the disease progresses, it leads to restricted ventilation, impaired gas exchange, respiratory symptoms, exercise limitation, poor quality of life and ultimately death .…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Of those who received a lung transplant, the median survival time was 55.5 months . The drug pirfenidone has been shown to slow the progression of IPF, but is not able to reverse septa thickening or alveolar distortion . Two recent 52‐week, randomized, phase 3 trials of the drug nintedanib found its use to be associated with a reduced decline in forced vital capacity (FVC), consistent with a slowing of disease progression .…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%
“…Idiopathic pulmonary fibrosis (IPF), featured by chronic exacerbating dyspnea and respiratory failure, affects 2–29 cases per 100,000 individuals [ 1 , 2 ]. The mean survival time of IPF after an initial diagnosis, ranging from 3.2 to 5 years, has remained unchanged in recent years despite vast improvement of novel drugs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%